PELABELAN AKAR RATA-RATA KUADRAT PADA GRAF LADDER〖 L〗_n DAN GRAF CORONA〖 P〗_n⨀K_2 - Mubarok, Azhar; Ratnasari, Lucia; Djuwandi, Djuwandi (MATEMATIKA, 2016)
A graph G with p vertices and q edges. A Root Square Mean Labeling of graph is an injective function from the set of vertices to the set with edge is the number of side on the graph such that when each edges is labeled by a function that defines as ceilling function or floor function from root square mean and , then the edge labels are distinct. For each of graphs that uses root square mean labeling is called as Root Square Mean graph. In this paper, the study is about root square mean labeling on Ladder graph, Corona graph . Then, we prove that and graph are included as the root square mean graph.